ANALISIS STRATEGI PROMOSI DALAM PENGEMBANGAN PARIWISATA (STUDI KASUS PADA PARIWISATA KABUPATEN PURWAKARTA): (STUDI KASUS PADA PARIWISATA KABUPATEN PURWAKARTA) - Jurnal COMMED; Mia Rachmayanti; Nofha Rina (Prodi Ilmu Komunikasi Universitas Putera Batam, 2018)
This research entitled “Analysis of Promotion Strategy as part of Tourism Development (Case Study of Tourism Purwakarta Regency)”. The purpose of this research is to discover a descriptive explanation of promotion strategy that is applied in Purwakarta Regency in order to promote their tourism sector. This research has taken place at the five top destinations which are Taman Air Mancur Sribaduga, Waduk Jatiluhur, Taman Surawisesa, Makam Syech Baing Yusuf, and Taman Pancawarna. Researchers conducted interviews with the Department of Tourism, the Office of Education and Operations Manager Grama tirta Jatiluhur as the parties who manage these tourist destinations.The method used in the research is qualitative descriptive study. Researcher collects data from conducting interviews, also supported by literature review, documentations, and observations. The research study indicate that Purwakarta Regency had applied promotion strategy activities such as target audience identification, determining communication objectives, planning the messages for the audience, choosing the suitable media and the accurate message references, collecting feedbacks, and setting the total amount of promotional budget.